2009
DOI: 10.1111/j.1468-1293.2009.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary drug resistance and transmission analysis of HIV‐1 in acute and recent drug‐naïve seroconverters in Singapore

Abstract: ObjectivesThe aim of the study was to elucidate primary drug resistance and transmission of HIV-1 in acute and recent drug-naïve seroconverters in Singapore. MethodsAcute and recent HIV-1 seroconverters were enrolled in the study. The HIV-1 polymerase (pol) gene was sequenced and used for genotypic drug resistance analysis and phylogenetic analysis. HIV-1 transmission clusters were inferred from phylogenetic clustering analysis. ResultsOf the 60 subjects analysed, 95% were men, and 73.3% were men who have sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…Infection with CRF01_AE as identified in this study has been confirmed through heterosexual transmission in China, and according to the recent reports MSM contact has become a major route of local CRF01_AE transmission in some cities of China and Singapore. [20][21][22] Our results suggest that MSM contact is becoming a major route of CRF01_AE transmission in China and that various forms of HIV transmission, including both homosexual and heterosexual behavior, likely exist among MSM of Liaoning province.…”
Section: Discussionmentioning
confidence: 93%
“…Infection with CRF01_AE as identified in this study has been confirmed through heterosexual transmission in China, and according to the recent reports MSM contact has become a major route of local CRF01_AE transmission in some cities of China and Singapore. [20][21][22] Our results suggest that MSM contact is becoming a major route of CRF01_AE transmission in China and that various forms of HIV transmission, including both homosexual and heterosexual behavior, likely exist among MSM of Liaoning province.…”
Section: Discussionmentioning
confidence: 93%
“…This result was similar to the findings of the study involving 60 recent seroconverters. 9 The transmission risk factor distribution comparing CRF01_AE, subtype B, and RF1 infection differed significantly ( p ¼ 0.001), with a higher proportion of RF1-infected patients compared to CRF01_AE or subtype B patients reporting MSM and bisexual risk (85% vs. 41% vs. 62%). The intermixing of subtypes within transmission risk groups and the higher prevalence of novel recombinants in high-risk groups mirror the developments observed in neighboring countries.…”
mentioning
confidence: 98%
“…However, no novel recombinant forms were detected. 9 This study aimed to update the HIV-1 molecular epidemiology and to determine the presence of intersubtype recombinants in Singapore. The three genomic regions chosen for sequencing would allow detection of all subtypes and CRFs in Southeast Asia identified to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PIs were introduced after 2008 by the Indian government in the ART program of India as second-line treatment regimens [2]. Resistance development may differ according to primary, secondary, or polymorphic mutations [7]. Primary mutation leads to reduced drug susceptibility directly, whereas secondary mutation leads to resistance in conjunction with primary mutation [8].…”
Section: Introductionmentioning
confidence: 99%